Corporate disclosure behavior during financial crises: Evidence from Korea - Kim, Yeonghyeon; Lee, Junyong; Lee, Kyounghun; Oh, Frederick Dongchuhl (Journal of Financial Stability, 2024)
We examine corporate disclosure patterns according to changes in firm states during financial crises in Korea. Using panel data on Korean listed firms from 1995 to 2019, we first confirm that they transparently (opaquely) disclose information when the change in return on assets is positive (negative) during crises. Moreover, we check that these disclosure patterns increase debt financing but are ineffective for equity financing. Finally, for chaebols with internal capital markets, we find that internal capital receivers provide transparent (opaque) disclosure of negative (positive) changes in their states. By contrast, providers show the opposite patterns. (JEL G01, G30, M40)